The Berenstain bears and the truth - Berenstain, Stan; Berenstain, Jan (New York : Random House, 1983)
Brother and Sister Bear learn how important it is to tell the truth after they accidentally break Mama Bear's most favorite lamp.
Keywords: Children's stories